Globalization and Economic Welfare: The Presence of an Unfair Gap Between Skilled Workers - Kondoh, Kenji (Mediterranean Journal of Social Sciences, 2012)
By focusing on the unfair gap between skilled workers of uniform quality, where unionized older workers are employedpermanently with higher wages, but younger workers fail to occupy permanent positions and are employed as uncertain temporary staffon lower wages, we investigate the effects of the two types of globalization caused by the increasing immigration of foreign unskilledworkers and trade liberalization. Under certain conditions, the immigration of unskilled workers might expand the income gap betweenthe two types of skilled workers, but it would have a positive effect on national welfare. Thus, with adequate income re-distributionpolicies by the government, immigration could be a welfare-improving policy. In contrast, although trade liberalization may reduce thewage gap between the two types of skilled workers, every worker may lose out, and the welfare-improving possibility of tradeliberalization may be relatively small. We also suggest that every worker may gain from an increase in the legal minimum wage.